Implementing Asta Protas through Kahoot in Islamic Religious Education at MAN 2 Bandung - Muhamad Rizza; Siti Nurul Mutiah; Fauzen Sugali (Penerbit Hellow Pustaka, 2025)
This study examines how Asta Protas Kemenag Berdampak, a national transformation framework initiated by the Minister of Religious Affairs, Nasaruddin Umar, can be operationalized through Kahoot in IRE at MAN 2 Kota Bandung. The research aims to analyze the alignment between Asta Protas’ teacher professionalism pillars and the pedagogical potential of game-based learning, particularly in enhancing engagement, assessment quality, and higher-order thinking. Employing a qualitative descriptive design, data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation of instructional materials. Analysis followed an interactive model of data collection, reduction, display, and interpretation. The findings indicate that Kahoot supports several key dimensions of Asta Protas, including pedagogical innovation, digital competence, and the development of meaningful learning experiences. Students exhibited strong behavioral, emotional, and cognitive engagement during Kahoot-based activities, while teachers demonstrated improved instructional planning and assessment literacy aligned with Bloom’s Taxonomy. Despite challenges related to digital infrastructure, teacher readiness, and the need for careful adaptation of religious content, Kahoot proved effective in fostering interactive, reflective, and value-oriented IRE learning. The study concludes that game-based learning can serve as a practical means to advance Asta Protas's goals and strengthen pedagogical transformation in madrasah education.